On the relationship between dynamic solubility, multi-atom bubble nucleation, irradiationinduced re-solution, and the bubble size distribution in Xe implanted Mo - Rest, D.; Yun, B. Ye; Insepov, Z. (Argonne National Laboratory, 2013)
U-Mo alloys are candidate fuels for both research and test reactors, as well as for advanced power reactors. A critical requirement for these candidate fuels is stable swelling behavior over their expected lifetime. In-reactor deformation of these materials is primarily driven by irradiation induced swelling where the primary component is fission gas (Xe and Kr) generated by decay of the primary fission products.